Carbohydrate intake for optimal performance in professional male & female tennis players - Martin, Lorena (ITF Coaching & Sport Science Review, 2015)
Many coaches and athletes underestimate the competitive advantage that proper carbohydrate intake can have on athletic performance. The intake and timing of carbohydrates may be the differentiating factor between victory and defeat. Remember there are many variables in the equation of optimal performance. In this article we will review some fundamentals on carbohydrate intake for optimal performance both in professional male and female tennis players.